Chronic Intestinal Pseudo-Obstruction Due to Incidentally Found Thymoma. Issue 5 (2nd May 2021) - Castaneda, Daniel; Miret, Rafael; Rajagopalan, Rajaganesh; Castillo, Michael; Gonzalez, Adalberto; Castro, Fernando
ABSTRACT: Chronic intestinal pseudo-obstruction is a severe gastrointestinal tract disorder mimicking a bowel obstruction with no mechanical causes. Our patient presented with bowel obstruction symptoms, and a thymoma was incidentally found during the diagnostic workup. After failing conservative management, the patient underwent exploratory laparotomy that showed negative results for a mechanical cause of obstruction. Laboratory workup was suggestive of paraneoplastic syndrome, and the patient was started on steroids and pyridostigmine course with symptom resolution. Thus, in patients with chronic intestinal pseudo-obstruction, paraneoplastic syndrome should be considered in the differential diagnosis.